EVALUATION OF DRUG MANAGEMENT AND SERVICE QUALITY OF SEVERAL PUBLIC PRIMARY HEALTH CARE PHARMACIES IN BANDUNG - Rizki Siti Nurfitria; Akhmad Priyadi; Sepriantina Sepriantina (School of Pharmacy Institut Teknologi Bandung, 2017)
ABSTRACTIn national health coverage era, public primary health care pharmacy must be supported by good drug management and service quality. These include human resources, pharmaceutical inventory management, and pharmacy service quality. This paper empirically evaluates the drug management that consist of planning, procurement, storage, distribution, and documentation aspects; and also how patients perceived pharmacy service quality. The research used observational descriptive design through triangulation method (observation, interview and checklist) for drug management evaluation in two primary public HCs and a self-completion Likert-scale SERVQUAL questionnaire was developed using a convenience sampling technique, given to 794 patients from three Primary public HCs that received medicine from pharmacy. This survey included five service quality dimensions; tangibility, reliability, responsiveness, assurance and empathy. The drug management in two primary public HCs had been categorized as having excellent management with the mean score 88.89% and 89.58% of all aspects and gap analysis showed mean gap score for five service quality dimensions of -0.98; -0.83 for responsiveness, -0.91 for reliability, -0.81 for assurance, -1.47 for empathy, -0.89 for tangibility, showing that patient expectation was still not met. Satisfaction level for pharmacy service was 79.53 % which is categorized as excellent. This paper provides useful information to primary public health care provider that the pharmacy unit is not providing service quality level expected by patients and needs improvement in many variables.Keywords: Drug Management, Service Quality, Pharmacy, Public Primary Health Care, EvaluationEVALUASI PENGELOLAAN OBAT DAN KUALITAS PELAYANAN KEFARMASIAN DI BEBERAPA PUSKESMAS DI KOTA BANDUNGABSTRAKDi era Jaminan Kesehatan Nasional (JKN), unit farmasi di fasilitas kesehatan tingkat pertama milik pemerintah dalam hal ini Puskesmas, harus didukung oleh pengelolaan obat dengan kualitas pelayanan yang baik. Hal ini meliputi sumber daya manusia (SDM), manajemen persediaan obat dan kualitas pelayanan farmasi. Penelitian ini mengevaluasi pengelolaan obat yang terdiri dari aspek perencanaan, pengadaan, penyimpanan, penyaluran, dan pencatatan serta mengevaluasi kualitas pelayanan farmasi di Puskesmas. Penelitian ini menggunakan desain observasional deskriptif melalui metode triangulasi untuk mengevaluasi pengelolaan obat dua Puskesmas (observasi, wawancara dan checklist) dan kuesioner SERVQUAL dengan skala Likert untuk mengevaluasi kualitas pelayanan yang diberikan kepada 794 pasien yang memperoleh obat di tiga Puskesmas secara convenience sampling berkaitan dengan lima dimensi kualitas: bukti langsung, kehandalan, daya tanggap, jaminan, dan empati. Pengelolaan obat di dua Puskesmas dikategorikan sangat baik dengan nilai rata-rata seluruh aspek 88,89% dan 89,58%. Hasil analisis celah menunjukkan nilai celah rata-rata seluruh dimensi kualitas -0,98; daya tanggap -0,83, kehandalan -0,91, jaminan -0,81, empati -1,47, bukti langsung -0,89, mengindikasikan bahwa harapan pasien belum terpenuhi. Tingkat kepuasan pasien terhadap kualitas pelayanan farmasi 79,53 % dan dikategorikan sangat baik. Penelitian ini memberikan informasi yang berguna bagi Puskesmas bahwa unit farmasi terkait belum dapat memberikan taraf kualitas pelayanan yang diharapkan oleh pasien dan memerlukan perbaikan dalam berbagai aspek.Kata kunci: Pengelolaan Obat, Kualitas Pelayanan, Unit Farmasi, Puskesmas, Evaluasi